Ultrafast dynamics of ionized biomolecules in aqueous solution observed via few-femtosecond transient absorption spectroscopy - Muhammad Shafiq Mohd Yusof (2020)
Few-femtosecond optical transient absorption spectroscopy elucidates the ionization-induced vibrational coherences and ultrafast dynamics of small biomolecules in aqueous solution. Strong-field ionization of such biomolecules by intense, few-cycle (~5 fs) laser pulses yields the radical species and the accompanying hydrated electron via multiphoton ionization. The vibrational coherences observed are due to the structural reorganization of the biomolecule in aqueous solution upon photoionization. Previous study on the photodetachment of aqueous phenoxide ion leads to wave packet dynamics of the phenoxyl radical along 12 different vibrational modes.[1] In our study, we studied the vibrational coherences of ionized tryptophan, tyrosine and phenol in aqueous solution that is accompanied by the structural reorganization of the molecule upon photoionization or photodetachment.